Imaging igneous intrusions in the lower crust on the Faroes and Hatton Bank margins using wide-angle Ocean Bottom Seismometer data. - Lewis, O. J.; White, R. S.; Christie, P. A. F. (2009)
Stacked seismic sections produced from wide-angle ocean bottom seismometers (OBS) show clear, strong P-wave reflections interpreted as igneous intrusions arriving from lower crustal and upper mantle depths on the Faroes margin. The lower-crustal reflectors are also seen on a coincident long- offset multi-channel (MCS) profile, though the upper mantle reflections are a new observation. Strong wide-angle reflections are also seen in OBS data from Hatton Bank profiles where no corresponding MCS profiles were shot. Applying this technique to the Hatton Bank data will allow us to image this section of the margin and determine if the structure seen in the Faroes MCS survey is present at other locations along the margin. Producing such images with conventional MCS data has proved difficult due to their necessarily limited offsets, and the presence of refractions and multiples at offsets beyond the first break of the sea-bed reflection. Adapting this technique to the OBS shear wave data may allow us for the first time to image sub-basalt structure with converted shear waves. Our results demonstrate the benefit of imaging wide-angle OBS data, since many OBS surveys have been employed solely to perform travel-time inversions. The data come from the integrated Seismic Imaging and Modelling of Margins (iSIMM) project shot in 2002 with wide- angle OBS surveys northeast of the Faroe Islands and across Hatton Bank. These areas contain flood basalts of the North Atlantic Igneous Province, making conventional seismic imaging challenging.